Discourse and the other : the production of the Afro-American text - Hogue, W. Lawrence, 1951- (e-Duke books scholarly collection., 1986)
The central thesis of Lawrence Hogue's book is that criticism of Afro-American literature has left out of account the way in which ideological pressures dictate the canon. This fresh approach to the study of the social, ideological, and political dynamics of the Afro-American literary text in the twentieth century, based on the Foucauldian concept of literature as social institution, examines the universalization that power effects, how literary texts are appropriated to meet ideological concerns and needs, and the continued oppression of dissenting voices. Hogue presents an illumi.